Maternal haemoglobin and perinatal outcome - Anjanappa, Bharathi; BH, Radhika; HG, Nataraja; Ramaiah, Renuka; P, Sathya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal anaemia is common medical disorder in developing countries. WHO defines anaemia as haemoglobin concentration of ≤11 g/dl. However, in developing countries like India, the lower limit is accepted as <10 g/dl, because of prevailing socio economic deprivation. Anaemia in pregnancy results in complications such as post-partum haemorrhage, infection, abruption placenta, preeclampsia, increased maternal mortality and morbidity. Also, it has reported to increase the risk of adverse perinatal outcome. The aim of this study was to evaluate the relation between haemoglobin levels in third trimester in pregnant women and adverse perinatal outcome. Methods: This is a prospective observational study conducted in the department of obstetrics and gynaecology, ESIPGIMSR, Rajajinagar, Bangalore. 218 women were enrolled in the study. All pregnant women with term gestation, singleton pregnancy, with live fetus willing to participate in the study were included. Exclusion criteria included antepartum haemorrhage, anaemia due to acute blood loss, multiple gestation, hypertensive disorders of pregnancy, stillbirths and IUDS. Haemoglobin estimation was done by cyanmethaemoglobin method. Paticipants in the study were divided into 2 groups; those with Hb<10 g/dl and those with Hb>10 g/dl. Results: Of 218 women, 69 had anaemia. The prevalence of anaemia was 31.65%; of which 84% had mild anaemia, 14.6% had moderate and only 1.4% had severe anaemia. Mean Hb levels were 12.04% among non-anaemic mothers and mean birth weight was 2.89 Kg whereas 9.14%, 2.18 kg in anaemic mothers respectively. In our study, 21% in anaemic group has birth weight <2.5 kg and only 0.06% in non-anaemic mothers (p<0.0012) 3.6 times higher. The risk of IUGR was 3.77 times higher, low APGAR score at 1 min was 3.8 times higher (p<0.0001), meconium stained liquor was 2.3 times higher and NICU admissions 2.96 times higher in anaemic mothers than non-anaemic mothers. Conclusions: Anaemia in pregnancy is one of the causes of poor perinatal outcome. Maternal anaemia is associated with the high risk of low birth weight, IUGR babies, low APGAR scores and NICU admissions and overall increase in perinatal morbidity. Hence proper antenatal care and counseling can reduce occurrence of anaemia in pregnancy.